EFFECTIVENESS OF ECOENZYME APPLICATION ON MUSTARD PLANTS (Brassica juncea L.) VAR. SAMHONG KING - Purnamasari, Retno Tri; Alim, M. Firmanul; Arifin, A. Zainul; Adi, Langgono (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Abstract   This study aims to determine the appropriate combination of Ecoenzyme administration in reducing urea use in the cultivation of samhongking mustard plants. This study was designed using a Randomized Block Design (RAK) involving 6 treatments with 4 replications, resulting in a total of 24 experimental units. The treatments tested were the administration of ecoenzyme combined with the administration of inorganic fertilizers: E0: Ecoenzyme Dose 0% + Urea Dose 0%; E1: Ecoenzyme Dose 100%; E2: Ecoenzyme Dose 50% + Urea Dose 50%; E3: Ecoenzyme Dose 75% + Urea Dose 50%; E4: Ecoenzyme Dose 25% + Urea Dose 50%; E5: Urea Dose 100%. The research data were analyzed using Analysis of Variance (ANOVA). If a significant effect is found, the analysis will be continued with the Honestly Significant Difference Test (HSD) at a significance level of 5%. The results of the study showed that the combination of 75% ecoenzyme + 50% urea application treatments provided growth and yield results that were close to the value of 100% urea application treatment, with 75% ecoenzyme application being able to reduce urea use by 50% with a yield of 562.93 g plant-1. Keywords: Ecoenzyme, Samhong King mustard greens, Urea